Variação sazonal da acumulação e fluxo noturnos de escalares em uma pastagem na região Amazônica - Santos, Daniel Michelon dos (2010)
Carbon dioxide and Radon nocturnal vertical accumulations over a pasture site at the Amazon region are investigated. The site is characterized by a strong thermal stability along the night, which is responsible for suppressing a good portion of the local turbulent mixing. Therefore, it is problematic to use techniques such as the eddy covariance for estimating nocturnal turbulent fluxes. The analysis considers the seasonal variation of the averaged nocturnal profiles between the wet season, from January to June and the dry season, from July to December. Radon profiles are analyzed with the purpose of helping to understand the physical processes affecting CO2 profiles, by comparing them to an independent and inert scalar. The analysis also considers the prevailing nocturnal wind direction. Results indicate that there is a large difference between CO2 fluxes and vertical gradients from one season to the other. Nocturnal CO2 vertical gradients between the two uppermost levels at the micrometeorological tower are often positive, indicating that the concentration increases with height. Such inversions are rarely observed on the Radon profiles, which follow the canonical form of a monotonical decrease with height. At the dry season, gradient inversions are more frequent and are, in general, associated to a direction inversion of the turbulent vertical CO2 flux, indicating that there is a downward vertical transport of this scalar at the measurement level. It causes flux convergence and an intense accumulation just above the surface. A cospectral analysis shows that such downward transport happens on the largest temporal scales of the motion, suggesting that it is associated to exchange between the surrounding forest and the pasture, in the form of mesoscale fluxes. Seasonally averaged behavior is well defined and uniform along the night, but case studies show that the processes are dominated by specific intense events. Radon fluxes measured during experimental field campaigns are used to estimate CO2 fluxes from the relationship between the vertical gradients of both scalars on six nights, three on each season. The comparison to the eddy covariance fluxes is satisfactory during the wet season, but poor during the dry season and the motives for that are discussed.